LED lights of various colors for comprehending the photoelectric effects phenomena - Prayogi, Soni; Silviana, Fitria (Majalah Ilmiah Teknologi Elektro, 2024)
In this project, a tool that can explain phenomena involving the photoelectric effect at laboratory scales is being developed. The purpose of this tool is to help users understand that the photoelectric effect, which causes electrons to move from a source of a negative voltage to a source of positive voltage, is not affected by light intensity but rather by a light source's frequency and wavelength. A photodiode is employed in the creation of this device as a light sensor, and when exposed to light, it moves electrons from the cathode to the anode, causing an electric current to flow. The voltage is delivered to the cathode, which is where the electrons leave, to calculate the stopping voltage. A graph showing the connection between the ADC value and the sensor output voltage is produced from the ongoing data gathering. Our results show that each color spectrum has a distinct voltage supplied to the photodiode leg (cathode). Additionally, the output voltage measured for each distinct wavelength was decreased the lower the photodiode's light intensity was.